EVALUASI PROSES PERENCANAAN STRATEGIS DINAS SOSIAL KOTA TANGERANG - Zito Kurnio Pamungkastono; Rihandoyo Rihandoyo (Journal of Public Policy and Management Review, 2016)
Strategic planning is not only applied in business, but also already implemented in public organizations such Social Departement of Tangerang, a technical institute of local government where the fundamental duty is to implement the preparation and execution of regional policy. Difficulties in projecting the future to face the changes that occur are the reason of the importance of strategic planning to solve the problem through programs and activities. The planning process is implemented properly will produce the right and excellent programs in order to achieve organization goals, therefore the strategic planning process must be observed at every stage, started from preparation until establishment so the organization is well prepared to face changes in the future. The preparation starts from presentation of the data and the determination of the role by analyzing the environment, until the strategic issue is attained in order to determine the right programs and activities. This study aims to analyze the strategic planning process in Social Departement of Tangerang in order to be evaluated at each steps of the plan in order to achieve the organization goal by using planned program and activity. The programs have to be well planned in order to reach the goal of Social Department of Tangerang effectively and efficiently.